Investment Training To Conquer Future Economic Challenges - Sabil, Alansah; Hidayah , Nenden Restu (Universitas Dehasen Bengkulu, 2025)
In order to answer increasingly difficult financial problems in the future. In this framework, the financial-based service strategy through awareness of understanding the basic principles related to fund placement, financial management, to the cruciality of systematic financial planning for the sustainability of life. The participants in this financial training are mostly students and Bengkulu residents. This financial-based service includes several stages: (1) preparation and planning; (2) Procurement of training; (3) Evaluation and Further Assistance. In addition to this, this training also examines crucial aspects from consumer behavior that can be an obstacle to saving and investment habits. Through the holding of PKM through this training, it is hoped that the younger generation can have the readiness and wisdom to answer economic problems, and can take the right investment steps for the future. This training is expected to be used as a start to realizing a society that has financial independence in the future.